Development of comprehensive heterodyne effect based inspection (CHEBI) method for inclusive monitoring of cracks - ÜNAL, MUHAMMET (ELSEVIER SCI LTD, 2018)
Early detection of developing structural cracks is extremely important in improving safety and reducing maintenance costs in structural, aerospace, chemical, petrochemical, gas, and oil industries. Nonlinear structural health monitoring methods, such as wave modulation spectroscopy (NWMS), can detect the cracks in their early stages of development. Such methods usually rely on the combination of a high and a low-frequency, vibroacoustic, excitation for defect detection. However, a priori knowledge of the characteristics of the crack is required for selection of the appropriate frequency combination. In this study, the Comprehensive Heterodyne Effect Based Inspection (CHEBI) method is proposed to address this issue. The CHEBI method applies ascending and descending broadband frequency sweeps simultaneously to study the response of the structure in wide ranges of frequencies in the time-frequency domain. Therefore, it eliminates the need for multiple experimental tests to find appropriate combinations of the high and the low-frequency components. The proposed method detected cracks from 1mm to 25mm in length on a dog-bone shaped aluminum specimen. These results confirm that the CHEBI can be successfully applied for detection of cracks with varying severities without the need for adjustment of the excitation frequencies.
Keywords: Structural Health Monitoring (SHM); Nonlinear Wave Modulation Spectroscopy; (NWMS); Heterodyning effect; Crack detection; Smart structures; WAVE MODULATION SPECTROSCOPY; WAFER ACTIVE SENSORS; DAMAGE DETECTION; ULTRASOUND SPECTROSCOPY; IMPACT DAMAGE; HEALTH; LOCALIZATION; COMPOSITES